Comorbidity of functional bowel disorders and obesity in terms of microbiome - E. S. Klimenko; N. L. Belkova; A. V. Pogodina; L. V. Rychkova; M. A. Darenskaya (Acta Biomedica Scientifica)
Bacterial ecosystem of the gut plays a fundamental role in the normal functioning of the metabolic and immune systems. Functional bowel disease and obesity are highly prevalent in the population and place a heavy burden on healthcare system. Both comorbidity and multimorbidity are considered to be common for obesity and intestinal functional disorders. Changes in the microbiota can be both the cause and consequence of each disease: intestinal functional disorder changes the composition of the microbiota, resulting in obesity, and vice versa. Intestinal functional disorders and obesity are characterized by a similar type of dysbiosis.The aim of the review is to analyze the research findings available to date in order to establish the relationship between the gut microbiome, functional bowel disease and obesity. The researches have shown that patients with intestinal functional disorders have a different gut microbiome than healthy individuals. For intestinal functional disorders, the general patterns of the intestinal microbiota composition were described, and the characteristic taxonomic groups of bacteria were identified. On the other side, it must be noted that there is no clear correlation between intestinal functional disorders and obesity in terms of the microbiota. This can be explained by the high heterogeneity of intestinal functional disorders, as well as by the lack of a unified approach to creating a study design, by different sizes of population samples and also by different diagnostic criteria. The necessity to determine the criteria in the development of the design of future studies is discussed.